The contribution to lichens and lichenicolous fungi of Rivnens'kiy Nature Reserve (CHORNOMORSKI BOTANICAL JOURNAL, 2022)
Data about lichens and lichenicolous fungi of the Rivnens'kiy Nature Reserve are reported. Totally, 69 species of lichens and lichenicolous fungi were listed. Among them Buellia griseovirens, C. cornuta, Lecanora saligna, L. symmicta, Micarea minuta, Parmeliopsis hyperopta, Placynthiella icmalea, P. uliginosa s. lat., Trapeliopsis flexuosa, T. granulosa, Stereocaulon condensatum, Thelocarpon intermediellum, Trapelia glebulosa, T. obtegens, Violella fucata are new to the Rivne region. Twenty-three species are new for the Rivnens'kiy Nature Reserve. Micarea minuta is recorded for the first time for Ukraine. This species was recently described from the Netherland. This species is characterized by an areolate greyish thallus, minute, 80–200 μm in diameter, greyish apothecia with sedifolia-grey pigment and absent of gyrophoric acid. Cladonia rangiferina, C. phyllophora are excluded from list of lichens of the Reserve. Lichen communities are presented by epiphytic species that grow on the bark of Pinus sylvestris, terricolous lichens on sand dunes and rare on stones (morena).
Keywords: Micarea minuta, biodiversity, Rivne region, Ukraine.